Uneven Development and Circular Causation - Gamal, Ahmad; Devina, Amanda (Universitas Indonesia, 2019)
This paper discusses the uneven development and detects the circular causation that occurs in the Kalibata area. Uneven development occurs between the street vendor trade area and Kalibata City trade area. The research method we use are: 1) literature study as theoretical basis to understand the uneven development theory and the occurrence of circular causation; 2) data collection by conducting interviews, observation, and direct mapping; 3) information processing where we used the data obtained to compare the differences in production processes between two regions. Kalibata City (formal area) and street vendor trade area (informal area) have different potential that generates the difference in production process. This article found that: 1) street vendor’s consumer facilities is simpler than Kalibata City; 2) street vendor area doesn’t have legal permit, thus making them susceptible to eviction, 3) street vendor is limited to the area beside the railway, 4) the tools used by the street vendors are less sophisticated than Kalibata City, and; 5) the street vendors have limited skills than the workers in Kalibata City. We also found there are 3 types of production of street vendors: low, mid, high complexity. Meanwhile, production process in Kalibata City is ran in a more structured and organized way. These differences trigger the developmental differences between these regions. Circular causation makes it worse. Kalibata City will continue to be able to develop its area, while PKL will be difficult to develop because its limitations.